2 - La gouvernance économique: quelles incidences sur le développement au Congo-Brazzaville? 10.4314/ad.v27i1.22150 - Ndinga, Mathias Marie A. (Africa Development, 2002)
After defining the concept of economic governance, this article compares Congo Brazzaville's performance in terms of economic growth and the population's well-being before and after the launching of reforms and then assesses the impact of governance on the levels of performance. The analysis came up with the following major conclusions: (i) in spite of the poor political and administrative governance that characterised the 1991-1999 period, the economic governance indicators sometimes attained a level higher than that of the first period. This, for instance, pertains to tax ratio, investment rate, the share of educational expenditures, as well as the health sector's percentage share of the total government expenditure, (ii) Similarly, from the viewpoint of the indicators for economic performance and the population's well-being, one notices that the inequality between workers employed in the different sectors was more pronounced in the first period than in the second. Indicators such as access to health services, safe drinking water and sanitation, are at their highest level in the second period more than in the first level, (iii) Finally, the impact of governance on growth and the people's well-being is generally more significant in the second period than in the first.